Immunohistochemical expression of CD8+ tumor-infiltrating lymphocytes and Foxp3 expression in colorectal carcinoma - Shaimaa Y Hammad; Hala I Awadallah; Manal A Badawi; Nermeen M Shaffie; Heba A.M. Salah; Dalia M Abouelfadl (Journal of the Arab Society for Medical Research, 2022)
Background/aim Colorectal cancer (CRC) is third among diagnosed tumors (6.1%) and second according to mortality (9.2%). Disease prognosis is determined not only by the histologic and molecular features of the tumor but also by the host response. Histologic distributions of tumor-infiltrating lymphocytes (TIL) in the microenvironment can be correlated with staging and prognosis of CRC patients. Abundance of CD8+ T lymphocytes has been associated with good prognosis in different types of solid tumors. The association between tumor cell expression of FoxP3 and tumor infiltration by FoxP3-expressing T lymphocytes with prognosis is still controversial. The aim of this study is to evaluate CD8+ TILs and expression of FoxP3 in CRC and to correlate their expression with patients’ clinicopathological parameters. Materials and methods Tumor paraffin blocks and clinicopathological data of 60 patients with CRC were obtained from the Pathology Department at Cairo University. The density of CD8 TILs and FoxP3 expression was assessed immunohistochemically and evaluated by image analysis in CRC specimens using area percentage parameter. The CD8+ cell tumor infiltrate and FoxP3 expression were classified into scanty, moderate, and abundant. Results CD8+ TIL in the present study was insignificantly correlated with the clinicopathological parameters, and no correlation was detected between FoxP3 and CD8 expression (P>0.05). However, FOXP3 expression was significantly correlated with tumor grade, nodal status, distant metastasis, tumor stage, and Dukes’ classification (P<0.01). Conclusion The presence of FoxP3 expression in CRC correlates with favorable pathological prognostic parameters. Cancer colon progression is influenced by host immune response. More studies are needed to assess the role of tumor microenvironment in CRC prognosis.